Aircraft lavatory wastewater surveillance for movement of antimicrobial resistance genes: a proof-of-concept study - Yawen Liu; Wendy J. M. Smith; Metasebia Gebrewold; Nicholas J. Ashbolt; Ishi Keenum; Stuart L. Simpson; Xinhong Wang; Warish Ahmed (Microbiology Spectrum)
ABSTRACT Long-haul flight aircraft wastewater may serve as a representative microbial footprint, often of mixed country origin, offering valuable insight into the movement of pathogens and antimicrobial resistance (AMR) on a global scale. Herein, we present a proof-of-concept for aircraft-based surveillance of AMR by investigating lavatory wastewater samples from 44 repatriation flights to Australia departing from nine countries. Profiles of pathogens including ESKAPE pathogens (Salmonella spp., Mycobacterium spp., Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, and Pseudomonas aeruginosa) and antibiotic resistance genes (ARGs) (aph(3’)-IIIa, blaNDM-1, blaCTX_M-1, blaKPC, ermB, qnrS, sul1, tetM, and vanA) were investigated along with traditional fecal indicator bacteria (Escherichia coli and Enterococcus spp.) and fecal/urine marker genes (Bacteroides HF183, Carjivirus, human polyomavirus, and a cryptic plasmid pBI143) using quantitative PCR (qPCR). Two fecal indicator bacteria (FIB) and four human fecal/urine marker genes were detected in all aircraft wastewater samples. Detection rates for ESKAPE pathogens ranged from 6.8% (S. aureus) to 84.1% (K. pneumoniae). Of all ARG targets, aph(3’)-IIIa, ermB, qnrS, sul1, and tetM were detected in all wastewater samples, whereas blaKPC and vanA were not detected in any of the samples. Results reflected geographic differences in ARG abundance originating from departure countries/continents and suggested a potential risk of importing ARGs that might be rare in local wastewater systems. The loss of nucleic acid targets was less than 10% over a 24 h incubation in the presence of disinfectants, suggesting that nucleic acids are resilient enough to persist in aircraft wastewater over the maximum duration of a flight.IMPORTANCEIn the context of international connectedness, aircraft-based wastewater surveillance should be viewed as a beyond-national tool to enhance global AMR management and foster international cooperation.